The prowess of platelets in immunity and inflammation - Koenen, Rory R. (Thrombosis and Haemostasis, 2016)
Platelets not only serve as essential haemostatic cells, they also have important roles in immune defence and inflammation. Despite not having a nucleus, platelets contain physiologically relevant amounts of RNA, which can be spliced and translated into functional proteins. In addition, platelets have the ability to bind to numerous other cells, such as leukocytes and vascular cells. During those interactions, platelets can modulate cellular responses, resulting in e. g. inflammatory activation or apoptosis. Recent studies have demonstrated that platelets can influence the outcomes of bacterial and viral infection, as well as the extent of tissue injury after ischaemia. Platelets also carry considerable amounts of cytokines and growth factors in their secretory granules, preformed for rapid secretion. Those properties in combination with the sheer amount of platelets circulating in the blood stream make them an important force in the immune response during health and disease. In this overview, recent findings concerning those interesting properties of platelets beyond haemostasis are discussed.
Keywords: Platelet immunology; inflammation; chemokines; adhesion molecules